2004
DOI: 10.1021/jf040164p
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Total Furocoumarins in Citrus Oils by HPLC Coupled with UV, Fluorescence, and Mass Detection

Abstract: Furocoumarins or psoralens represent a class of photosensitizers whose use level is likely to be restricted to 1 ppm in cosmetic products by the EU. A reversed-phase HPLC method was developed to separate the 15 main furocoumarins present in citrus oils. Quantification by UV, fluorescence, or mass detectors was compared in terms of linearity and limit of detection. Cold-pressed oils of different citrus species were analyzed using this method. This method could be implemented in quality control laboratories equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 20 publications
7
105
0
Order By: Relevance
“…Oxygen-containing heterocyclic metabolites, consisting of coumarins, furanocoumarins, and polymethoxylated flavones, were present in the oil at 4.9% (w/v) before the peel started yellowing (70 mm ED) and then decreased slightly to 4.1% (w/v) in oil obtained from mature fruit (100 mm ED; Table I). This is consistent with prior studies (McHale and Sheridan, 1989;Frérot and Decorzant, 2004;Dugo et al, 2010). Carotenoids had been described as minor components of cold-pressed Citrus oils (Dugo et al, 2006) but were undetectable in our microcapillary-collected grapefruit oil samples (Table I).…”
Section: Chemical Analysis Of Grapefruit Peel Essential Oil Collectedsupporting
confidence: 92%
See 2 more Smart Citations
“…Oxygen-containing heterocyclic metabolites, consisting of coumarins, furanocoumarins, and polymethoxylated flavones, were present in the oil at 4.9% (w/v) before the peel started yellowing (70 mm ED) and then decreased slightly to 4.1% (w/v) in oil obtained from mature fruit (100 mm ED; Table I). This is consistent with prior studies (McHale and Sheridan, 1989;Frérot and Decorzant, 2004;Dugo et al, 2010). Carotenoids had been described as minor components of cold-pressed Citrus oils (Dugo et al, 2006) but were undetectable in our microcapillary-collected grapefruit oil samples (Table I).…”
Section: Chemical Analysis Of Grapefruit Peel Essential Oil Collectedsupporting
confidence: 92%
“…Studies on the nonvolatile constituents of Citrus essential oil began in the 1960s (for review, see Dugo et al, 2009), but reliable quantifications for grapefruit were not reported until much later (McHale and Sheridan, 1989;Frérot and Decorzant, 2004;Dugo et al, 2010). All of these studies used cold-pressed grapefruit oil for phytochemical and chemometric analyses.…”
Section: Chemical Analysis Of Grapefruit Peel Essential Oil Collectedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, umbelliferone-dimethylallyltransferase activities were reported in cultured parsley (Petroselinum crispum) cells, Ruta graveolens, and Ammi majus, and plastidial localization of the enzyme activity is also reported (Ellis and Brown, 1974;Dhillon and Brown, 1976;Tietjen and Matern, 1983;Hamerski and Matern, 1988;Hamerski et al, 1990). In addition, bergaptol 5-Ogeranyltransferase activity, which yields bergamottin, a major coumarin derivative, was characterized using the microsomal fraction of lemon (Citrus limon) peel flavedo, the outer part of the lemon fruit (Frérot and Decorzant, 2004;Munakata et al, 2012). In the lemon flavedo, 8-geranyltransferase activity for umbelliferone was also detected (Munakata et al, 2012).…”
mentioning
confidence: 99%
“…One was identified as imperatorin by means of the GC/MS method, for the following analysis. 10,11 The prepared imperatorin was used for treating rats.…”
Section: Preparation Of Imperatorinmentioning
confidence: 99%